Perceptions of Threat Risk Frequency and Impact on Construction Projects in Ghana: Opinion Survey Findings - Nicholas Chileshe; Adwoa Boadua Yirenkyi-Fianko (Journal of Construction in Developing Countries, 2011)
Threat risks are experienced by all stakeholders in a construction project. Although the nature of these risks is understood, less is known about their likelihood of occurrence and potential impact. This study explored these elements of risk by using an opinion survey approach to collect data from 103 professionals (clients, consultants and contractors) in the Ghanaian construction industry. Significant differences were found between the perceptions of these sub-groups regarding the likelihood of occurrence of threat risks in five categories: construction method; price inflation; exceptional weather; ground conditions and site contamination; and poor communication among the project team. The contractors rated ‘construction methods’ higher than did the clients, and they also rated ‘exceptional weather’ higher than either the clients or the consultants. On the other hand, consultants rated ‘price inflation’ higher than the clients. Significant differences between the sub-groups were also found regarding the potential impact of the threat risk of price fluctuation. The consultants rated the ‘price fluctuation’ threat risk higher than either the contractors or the clients. These findings suggest that despite the existence of remedial strategies to protect some of the stakeholders from these risks, there is a fear of being blacklisted, thus compromising future opportunities (especially among contractors) should legal action be taken to redress the identified problems (such as such delayed payments). The following implications are drawn: One of the suggested recourses is the introduction of bespoke rather than standard contracts, as these might introduce contract flaws and contribute towards helping the project stakeholders monitor these potential risks and take appropriate action.